Cough duration, energy and sound frequency in COVID-19 patients: the spectral analysis results - Andrey V. Budnevsky; Djuro Kosanovic; Evgeniy S. Ovsyannikov; Oleg N. Choporov; Alexander V. Pertsev; Sofia N. Feigelman; Tatiana A. Chernik; Alexey V. Maksimov; Galina G. Prozorova; Svetlana A. Kozhevnikova; Roman E. Tokmachev; Anastasiya V. Belyakova; et al. (BMC Pulmonary Medicine)
Abstract Background. Cough is one of the most common clinical manifestations of COVID-19. Objective of our study was to perform analysis of cough duration, energy and sound frequency in COVID-19 patients, compared to induced cough in controls and the cough in asthma and chronic obstructive pulmonary disease (COPD) patients. Methods. The following characteristics of cough sounds were obtained: duration, Q coefficient - low/medium-frequency energy (60–600 Hz) to high-frequency energy (600–6000 Hz) ratio, and frequency of maximum sound energy. The cough was divided into three phases and assessment of characteristics was applied to the entire coughing act and to each phase separately in controls and patients with COVID-19, asthma and COPD. Results. The cough sounds of COVID-19 patients were characterized by a shorter duration, a predominance of high-frequency energy and higher maximum frequency of the energy, compared with the induced cough of controls. However, the frequencies of the maximum sound energy of the individual cough phases did not differ significantly, as did the duration of the first phase. In addition, the significant differences were demonstrated in some time-frequency parameters of cough sounds in the patients with asthma and COPD as compared to COVID-19 patients. Conclusion. Therefore, we have shown the distinction between the cough characteristics of COVID-19 patients compared to controls and patients with asthma or COPD.